HIPER-REALITAS VISUAL - , Martadi (Institute of Research and Community Outreach - Petra Christian University, 2003)
At the last of twentieth century%2C the tecnology growth has changed the world display which is formed by the electronic images every where (television%2C film%2C game%2C virtual reality%2C digital photo%2C internet). The digital technology growth has brought the human fantasia throughout the limit%2C created the three dimensioan rooms with the object inside%2C until the stage of the visual reality has been passed throuhg by the visual image manipulation%2C hence%2C it is like the human being step from the real to the fantastic world%2C an imagination which seems like the truth. The problem becomes more complex when we have to face the reality that the technology growth brings the negative impacts. While the tecnology could be satisfy the human desire%2C giving an esctasy fantasia%2C then the moral values is nullified one by one. Criminals%2C pornography%2C come up freely wear the newest formats. Abstract in Bahasa Indonesia : Perkembangan teknologi pada akhir abad ke-20 telah merubah wajah dunia yang dibentuk oleh riuh rendah citraan elektronik (televisi%2C film%2C game%2C virtual reality%2C foto digital%2C internet). Perkembangan teknologi digital telah membawa fantasi manusia menembus batas%2C menciptakan ruang-ruang tiga dimensi berikut obyek-obyek di dalamnya%2C sampai pada tahap di mana realitas visual telah dilampaui dengan manipulasi pencitraan visual%2C sehingga seolah manusia melangkah dari dunia nyata menuju dunia fantasi%2C dunia maya yang tampak nyata. Permasalahannya menjadi semakin rumit ketika kita dihadapkan pada realita bahwa perkembangan teknologi tersebut membawa pula dampak negatif. Pada saat teknologi memuaskan hasrat/nafsu manusia%2C memberikan pesona ekstasi%2C maka nilai-nilai moral seakan rontok satu per satu. Hyper-reality%2C Visual.